Supreme law of the land? debating the contemporary effects of treaties within the United States legal system - Fox, Gregory H. 1961-; Dubinsky, Paul R.; Roth, Brad R. (Cambridge University Press, 2017)
How do treaties function in the American legal system? This book provides a comprehensive analysis of the current status of treaties in American law. Its ten chapters examine major areas of change in treaty law in recent decades, including treaty interpretation, federalism, self-execution, treaty implementing legislation, treaty form, and judicial barriers to treaty enforcement. The book also includes two in-depth case studies: one on the effectiveness of treaties in the regulation of armed conflict and one on the role of a resurgent federalism in complicating US efforts to ratify and implement treaties in private international law. Each chapter asks whether the treaty rules of the 1987 Third Restatement of Foreign Relations Law accurately reflect today's judicial, executive, and legislative practices. This volume is original and provocative, a useful desk companion for judges and practicing lawyers, and an engaging read for the general reader and graduate students
Title from publisher's bibliographic system (viewed on 18 Sep 2017)
Machine generated contents note: Introduction Paul R. Dubinsky, Gregory H. Fox and Brad R. Roth; 1. Treaties in US law from the Founding to the Restatement (Third) Mark Janis and Noam Wiener; 2. Treaties and the Third Restatement Gregory H. Fox; 3. Competing models for treaty interpretation: treaty as contract, treaty as statute, treaty as delegation Paul R. Dubinsky; 4. Self-execution Ingrid Wuerth; 5. Treaties, federalisation, and the contested legacy of Missouri v. Holland Margaret McGuinness; 6. Recent trends in US treaty implementation David P. Stewart; 7. The treaty and its rivals: making international agreements in US law and practice Michael D. Ramsey; 8. Judicial barriers to the enforcement of treaties Roger P. Alford; 9. Case study no. 1: exploring US treaty practice through a military lens Geoffrey Corn and Dru Brenner-Beck; 10. Case study no. 2: private law treaties and federalism: can the United States lead? Paul R. Dubinsky; 11. Conclusion Gary B. Born
Description based on publisher supplied metadata and other sources
Keywords: United States / Congress / Powers and duties; Treaties; Treaty-making power / United States; United States / Foreign relations / Treaties